HISTOLOGY. IS IT HARD TO LEARN IT TODAY? - Skybinsʹka, T.R.; Sokurenko, L.M.; Shobat, L.S.; Чайковський, Ю.Б. (World of Medicine and Biology, 2017)
The purpose of our study was to review the teaching of histology, cytology and embryology (HCE) and the progress of the medical department students at the HCE chair of Kiev Medical Institute in the 30s of the 20th century and the O.O. Bogomolets National Medical University in our time. Comprises documents from the archives and publications that allowed us to look at the effectiveness of education at Kiev Medical Institute in the 30s of the 20th century. Various methods for improving the progress and quality of students' training were considered and the current progress of the O.O. Bogomolets National Medical University medical department students analyzed, taking into account those factors that, in our opinion, affect the retention of HCE.The obtained results allowed us to trace changes in the progress of medical departments students at different time periods. The number of students who passed HCE with the "excellent" and "excellent" and "good" marks decreased, while the number of students who got the "unsatisfactory" mark increased. This is explained by the amount of information that needs to be learned. In the 30s of the last century, the students had to study the basics of classical histology: to describe the microscopic structure of cells, tissues and organs at the light-optical level. Today, many other components have been added to this.The development of modern HCE requires a lot of work. Joint efforts of the departments of HCE and students will enable them to overcome difficulties. This should be remembered in the context of the ongoing reform in medicine and medical education.
Keywords: medicine; students; quality of teaching; historical aspects of medicine development in Ukraine; analysis of learning achievement